Post‐operative incidence of lymphedema after RARP with or without extended pelvic lymph node dissection in a cohort study - Andries Clinckaert; Laura Ysenbaardt; Annabel Bijnens; Charlotte Van Calster; Inge Geraerts; Steven Joniau; Nele Devoogdt; Luc Bijnens; Wouter Everaerts (BJUI Compass)
Abstract Objectives Lymphedema of the lower limbs and pubic area is a potential complication following extended pelvic lymph node dissection (ePLND) during robot‐assisted radical prostatectomy (RARP). The incidence of lymphedema after ePLND has not been systematically reported in the literature. This study aimed to determine the incidence of lymphedema, describe its clinical characteristics and identify specific risk factors in patients undergoing RARP with or without ePLND. Methods A retrospective cohort study was conducted at a tertiary referral centre between April 2016 and July 2020. Structured electronic case report forms (eCRFs) integrated into the electronic health record system were used to document intraoperative, perioperative and postoperative data. The primary endpoint was the incidence of lymphedema. Secondary endpoints included risk factors for and localization of the postoperative lymphedema. Results A total of 500 patients who underwent RARP were included, with 301 patients undergoing ePLND and 199 patients without any form of PLND. Median follow‐up period was 18 (range 3–49) months. Seventy‐eight out of 301 (26%) of patients who underwent ePLND developed lymphedema, compared to only 2 out of 199 (1%) patients without ePLND. In most patients (49/301, 16%), lymphedema was mild (grade 1), whereas 29 patients (10%) developed grade 2 lymphedema. Twenty‐six patients (9%) received decongestive lymphatic therapy. The most frequent site of lymphedema occurrence were the lower (54%) and the upper legs (40%). The number of nodes removed during RARP was identified as a risk factor for post‐operative lymphedema (OR 1.04; p < 0.05). Conclusions In this cohort study, approximately one in four patients undergoing RARP with ePLND developed lower limb and/or midline oedema, whereas one in ten patients started decongestive lymphatic therapy for symptomatic lymphedema. These findings provide valuable information for patient counselling about the potential benefits and risks of ePLND.